Seed rain alteration related to fire and grazing history in a semiarid shrubland - Leder, Cintia Vanesa (2015)
In arid environments, vegetation is distributed in patches. Herbivory and fires promote changes and seed rain plays a key role in the soil seed bank and the colonization of new spaces. This study focuses on the effect of different land use histories on the spatial and temporal seed rain distribution in Patagonia. We placed traps to capture seed rain of perennial grasses, shrubs and annual forage dicots at five sites with different grazing and fire histories. With grazing and fire seed rain diversity is higher than in absence of disturbances. Functional groups seed rain in vegetation patches did not show differences between sites, but at the interpatch level, grazing increased shrub seed and decreased perennial grass seed in the seed rain. Fire decreased the effects of grazing on shrub seed rain, but did not change its effects on perennial grasses. Shrub species showed a minimum abundance in the seed rain in the undisturbed site. Our re- sults suggest that changes described for vegetative attributes are reflected in the seed rain, and this could reinforce the patch-interpatch pattern; fire did not reduce the grazing effects because it decreased the seed rain of the preferred grasses and increased the less preferred ones.